Studi ‘Ulum Al-Qur’an Perspektif Insider/Outsider - Syaiful Anas; Muhammad Miftah; Bilal Ibn Naim Baker (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2026)
The study of ‘Ulum al-Qur’an has undergone significant development along with the advancement of Islamic studies, both within the Islamic intellectual tradition and in Western academic environments. This development has led to two major perspectives in understanding the Qur’an, namely the insider and outsider perspectives. The insider perspective positions the Qur’an as the word of God that serves as the foundation of faith and guidance for life, while the outsider perspective tends to view the Qur’an as an object of scientific inquiry that can be studied through various academic approaches. This study aims to analyze the study of ‘Ulum al-Qur’an from insider and outsider perspectives and to identify the characteristics, approaches, and implications of both perspectives. This research employs a qualitative approach with a library research design. Data were collected through documentation techniques from various scientific sources, including books, national journals, international journals, and other relevant literature. The data were analyzed using content analysis through data reduction, data presentation, and conclusion drawing. The findings indicate that the insider perspective emphasizes a normative-theological approach oriented toward strengthening faith aspects, whereas the outsider perspective emphasizes a historical-critical approach oriented toward scientific analysis. Although both perspectives differ fundamentally, they contribute to the development of ‘Ulum al-Qur’an studies and may complement each other in producing a more comprehensive understanding. Keywords: ‘Ulum al-Qur’an, insider, outsider, Islamic studies, epistemology.